Exploring the Persuasive Power of Multimodality in the Rollover Reaction Dewdrop Advertisement - Asyifa Alfahira Balqis; Suyudi, Ichwan (ITScience (Information Technology and Science), 2024)
Advertisement is a powerful medium that relies on various elements to convey its intended message to the target audience. When exploring the effective communication of messages in advertisements, the intricacy of meaning involves both verbal and non-verbal elements. To grasp the influence and significance of a text that incorporates multiple modes—for instance verbal, visual, and aural—a thorough analysis of an advertisement using multiple modes is essential to comprehend the nuanced layers of meaning. In creating the great advertisement, there are some reason for Makeup Company to take full advantage of using Instagram in promoting their brand and also the product. This research aims to analyze the multimodal resources in the Rollover Reaction’s makeup product namely Dewdrop advertisement on Instagram based on five semiotic multimodal systems proposed by Anstey & Bull (2018). This research applies a qualitative method and descriptive approach. The data were taken in the form of an image that was taken from a screenshot of the Rollover Reaction advertisement on Instagram. The result shows that there are three aspects of the multimodal system contained in this advertisement, including linguistic, visual, and spatial. These three aspects are mutually connected to convey the messages of Rollover Reaction's Instagram page and also promote and introduce this unique brand.